2017
DOI: 10.3892/ol.2017.6017
|View full text |Cite
|
Sign up to set email alerts
|

Lunasin: A promising polypeptide for the prevention and treatment of cancer

Abstract: Abstract. Strategies for the treatment of cancer remain unsatisfactory due to the poor understanding of the complicated underlying molecular mechanisms of carcinogenesis. A number of types of cancer exhibit a marked association with dietary habits and lifestyles. Therefore, the modulation of dietary habits or lifestyles may be an effective strategy for preventing the formation and progression of cancer. Proteins and polypeptides from soybean have been developed as healthcare products due to their marked activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Thus, it might have a role in transcription regulation. A tri‐peptide, RGD (Arg‐Gly‐Asp; residues 32–34), within the lunasin peptide which is a cell‐adhesion module and promotes intracellular accessibility of lunasin by functioning as an extracellular matrix, whereas, a stretch of nine Asp residues are present at the C‐terminus involved in anti‐mitotic functions (Wan et al, ). However, in a study by Hernández‐Ledesma et al, it was reported that although lunasin is a long peptide, its complete primary sequence along with its resulting secondary and tertiary structures are required to exhibit the anti‐inflammatory properties.…”
Section: Anti‐inflammatory Peptides and Structural Requirementsmentioning
confidence: 99%
“…Thus, it might have a role in transcription regulation. A tri‐peptide, RGD (Arg‐Gly‐Asp; residues 32–34), within the lunasin peptide which is a cell‐adhesion module and promotes intracellular accessibility of lunasin by functioning as an extracellular matrix, whereas, a stretch of nine Asp residues are present at the C‐terminus involved in anti‐mitotic functions (Wan et al, ). However, in a study by Hernández‐Ledesma et al, it was reported that although lunasin is a long peptide, its complete primary sequence along with its resulting secondary and tertiary structures are required to exhibit the anti‐inflammatory properties.…”
Section: Anti‐inflammatory Peptides and Structural Requirementsmentioning
confidence: 99%
“…Its chemical structure was previously described [19]. Lunasin was extensively studied for various indications [5,6,9,20,21,22,23,24,25,26,27,28]. …”
Section: Methodsmentioning
confidence: 99%
“…Although residues one to 22 of lunasin have no known biological function, its residues 23 to 31 form a helical structure with structural homology to a conserved region of chromatin‐binding proteins (Galvez et al., 2001). The residues 32 to 34 of lunasin are a tripeptide (RGD) with cell adhesion motif and the remaining nine ASP residues at the C‐terminus that make up the whole lunasin peptide contribute to the antimitotic functions (Galvez et al., 2001; Wan et al., 2017). Noticeably, many peptides reported in the literature shown in Tables 1–6 (e.g., ALPQYLKTVYQHQK, FQQQYYPGLSN, and VLAEWKQKYEESQAELEGAQKEARS obtained from fermented milk, rice protein byproduct, and zebra blenny muscle proteins, respectively) contain a considerable amount of glutamine residues with hydrophobic and polar amino acids at the N‐ and C‐terminus, respectively.…”
Section: Structure–activity Relationship Of Bpsmentioning
confidence: 99%